2021
DOI: 10.1109/jphot.2021.3101480
|View full text |Cite
|
Sign up to set email alerts
|

Sheet Charge Engineering Towards an Efficient Hole Injection in 290 nm Deep Ultraviolet Light-Emitting Diodes

Abstract: The hole injection efficiency is one of the bottlenecks that restricts the external quantum efficiency (EQE) and optical power of AlGaN-based deep ultraviolet light-emitting diodes (DUV LEDs). The polarization-induced positive sheet charges at the last quantum barrier (LQB)/electron blocking layer (EBL) interface reflect the holes back to the p-type layer and weaken the hole injection capability into the active region. In this work, we designed and incorporated a polarization-engineered AlxGa1-xN/AlyGa1-yN sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Single AlN layer [19] and ultrathin AlGaN/AlInN heterojunction [20] inserted between the LQB and p-EBL were proposed to enhance hole injection by utilizing intraband tunneling process for holes. Refs [21]- [23] reported that introducing AlGaN/AlGaN superlattice insertion layer at the LQB/p-EBL interface can increase the effective barrier height for electrons and decrease the effective barrier height for holes. However, the aforementioned structures place high demands on precise control of epitaxial process for AlGaN-based DUV LEDs.…”
mentioning
confidence: 99%
“…Single AlN layer [19] and ultrathin AlGaN/AlInN heterojunction [20] inserted between the LQB and p-EBL were proposed to enhance hole injection by utilizing intraband tunneling process for holes. Refs [21]- [23] reported that introducing AlGaN/AlGaN superlattice insertion layer at the LQB/p-EBL interface can increase the effective barrier height for electrons and decrease the effective barrier height for holes. However, the aforementioned structures place high demands on precise control of epitaxial process for AlGaN-based DUV LEDs.…”
mentioning
confidence: 99%